Лексика письменных текстов как сокровищница культуры носителей языка и источник ее повышения - Матвеева, Наталия (Studia Rossica Posnaniensia, 2014)
The article focuses on the origin of and studies obligatory written texts which are regarded as a source of knowledge about the culture of native speakers of ancient Indian, ancient Chinese, classic Greek and Latin as well as Arabic and eastern Slavic languages. Much attention is paid to the theory of “correctness” as regards the necessity for native speakers to improve their cultural and linguistic literacy. This article shows the necessity of identifying a specific field within lexicology, i.e. “glossology”, which focuses on analyzing semantically difficult lexis (obsolete words, terms, neologisms, etc.) in obligatory written texts. As a result of a theoretical study of such lexemes, a special field within lexicography, i.e. “glossography”, was identified; this field deals with studying and developing the theoretical and practical basis for creating dictionaries of lexical-semantic difficulties in written texts.